Feeding Potential of Fruit Fly (Diptera: Tephritidae) on Different Artificial Diets under Laboratory Conditions - B Satheesh (Global Journal of Plant and Soil Sciences, 2025)
Fruit flies are a serious pest of fruits and vegetables. They can lose to the GDP of any country by damaging the fruit and vegetable industry. It has a great economic threat to worldwide. In the present study, five different artificial diets were used and the life cycle (Fecundity, egg hatchability, larval development, pupal formation, adult emergence, and sex ratio) of Bactrocera zonata was checked. Results showed that diet V (100ml water, 18.8g sugar, 0.07 sodium benzoate, and 5 g beaker yeast) gives significant results in all life stages of the fruit fly. Fecundity, egg hatchability, larval development, pupal formation, adult emergence, and the sex ratio was ob- served maximum in the diet V and diet I (100ml water, 18.8g sugar, and 0.07sodium benzoate) gives minimum means results of the life cycle of B. zonata. The results of this study showed that all types of diets had a significant effect on the B. zonata life cycle but diet 5 showed more significant (p<0.05) results than other artificial diets.